Globalisation: Re-Reading Its Impact on the Nation-State, the University, and Educational Policies in Europe - Kwiek, Marek (My University, 2009)
The paper re-reads the complex and changing relationships between the university and the nation-state, and between national and supranational (EU-level) educational policies in Europe. It is focusing on long-term consequences of globalisation -related presures on Europeanation-states with respecto national educational policies. It assesses the indirect impact of globalisation on European universities (via reformulating the role of the nation-state in the global economy), and a direct impact of Europeanisation — as a regional response to globalisation — on universities (via new EU-level discourse on the changing role of universities in knowledge economy). New educational policies promoted at the EU-level are viewed as delinking the nation-states and public universities. The paper re-reads the changing institution of the nation-state and its changing educational policies in the context of globalisation (sections 2 and 3) and in the specific, regional context of Europeanisation (section 4). It follows from presenting three major positions taken in the literature with respect to transformations of the nation-state under globalisation to presenting the process of de-linking traditional universities and the nation-state and its practical dimension at the EU level at which the role of universities is viewed from the perspective of larger social and economic agenda (called the Lisbon strategy for growth and jobs). The major lesson to be drawn from this re-reading exercise is that there are complex and often contradictory relationships between globalisation as a process affecting the nation-states, changing national educational policies, and national and EU-level policies — which all transform the future role(s) of European universities. In sum, current challenges European universities face, and current policy solutions European governments suggest, are best viewed in the overall context of globalisation. National governments are responding to both globalisation and Europeanisation: policies and strategies they produce, instruments they use, and contradictions they cope with are best reread in this context.
Keywords: globalization; higher education; European universities; welfare state; nation-state; welfare reforms; public sector reforms; Europeanisation; European integration; European Commission; Lisbon Strategy; educational policies; global forces; modern university; Wilhelm von Humboldt; national university; globalists; globalism; supranational policies; public sector; higher education research